2016
DOI: 10.1016/j.bpj.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Open-Loop Control of Oxidative Phosphorylation in Skeletal and Cardiac Muscle Mitochondria by Ca2+

Abstract: In cardiac muscle, mitochondrial ATP synthesis is driven by demand for ATP through feedback from the products of ATP hydrolysis. However, in skeletal muscle at higher workloads there is an apparent contribution of open-loop stimulation of ATP synthesis. Open-loop control is defined as modulation of flux through a biochemical pathway by a moiety, which is not a reactant or a product of the biochemical reactions in the pathway. The role of calcium, which is known to stimulate the activity of mitochondrial dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…High‐resolution respirometry determines mitochondrial function by measuring mitochondrial oxygen consumption after a bolus injection of ADP. Since the experiment is performed in a sealed chamber, all oxygen consumed after a bolus of ADP is directly related to the production of ATP through complex IV of the mitochondrial respiratory chain . While this measure is performed in non‐physiological conditions (ie, saturating O 2 ), it permits comparison of maximal aerobic function without confounding influences present in the cellular environment.…”
Section: Mitochondrial Function and Skeletal Muscle Metabolism In Metsupporting
confidence: 53%
“…High‐resolution respirometry determines mitochondrial function by measuring mitochondrial oxygen consumption after a bolus injection of ADP. Since the experiment is performed in a sealed chamber, all oxygen consumed after a bolus of ADP is directly related to the production of ATP through complex IV of the mitochondrial respiratory chain . While this measure is performed in non‐physiological conditions (ie, saturating O 2 ), it permits comparison of maximal aerobic function without confounding influences present in the cellular environment.…”
Section: Mitochondrial Function and Skeletal Muscle Metabolism In Metsupporting
confidence: 53%
“…also reported that mitochondrial NADH level was almost insensitive to Ca 2+ when pyruvate and malate were used as mitochondrial substrates (Vinnakota et al . , b ). The present simulation study is in line with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Beard and his colleagues discovered from experiments using isolated rat heart mitochondria that Ca 2+ at the physiological level did not stimulate flux of NAD(P)H synthesis nor ΔΨ over a wide range of VO 2 (Vinnakota et al . 2011, 2016 b ). Although species differences in intracellular Ca 2+ handling (Bassani et al .…”
Section: Parallel Activation Mechanismmentioning
confidence: 99%